2014
DOI: 10.1039/c3cc49198f
|View full text |Cite
|
Sign up to set email alerts
|

Benzoselenadiazole-based responsive long-lifetime photoluminescent probes for protein kinases

Abstract: Benzoselenadiazole-containing inhibitors of protein kinases were constructed and their capability to emit phosphorescence in the kinase-bound state was established. Labelling of the inhibitors with a red fluorescent dye led to sensitive responsive photoluminescent probes for protein kinase CK2 that emitted red light with a long (microsecond-scale) decay time upon excitation of the probes with a pulse of near-UV light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
(27 reference statements)
2
23
1
Order By: Relevance
“…[7,15] We have previously shown that intensity of light emission from the excited triplet state of several sulfur-or selenium-comprising heteroaromatic purely organic phosphors could be substantially enhanced by covalent conjugation of a bright fluorescent dye whose absorption spectrum overlap with the phosphorescence spectrum of the phosphor. [16][17][18][19] Upon excitation of the phosphor moiety with a pulse of near-UV-radiation in such tandem luminophore in complexes with a protein kinase (PKs), the tandem probe exhibits long lifetime luminescence (luminescence lifetime τ in 20 -300 μs range). In these complexes the ATP-binding pocket of PK restrains molecular motions and the protein shields the exited triplet state of the donor phosphor from quenching by dissolved molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7,15] We have previously shown that intensity of light emission from the excited triplet state of several sulfur-or selenium-comprising heteroaromatic purely organic phosphors could be substantially enhanced by covalent conjugation of a bright fluorescent dye whose absorption spectrum overlap with the phosphorescence spectrum of the phosphor. [16][17][18][19] Upon excitation of the phosphor moiety with a pulse of near-UV-radiation in such tandem luminophore in complexes with a protein kinase (PKs), the tandem probe exhibits long lifetime luminescence (luminescence lifetime τ in 20 -300 μs range). In these complexes the ATP-binding pocket of PK restrains molecular motions and the protein shields the exited triplet state of the donor phosphor from quenching by dissolved molecular oxygen.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date there is no general strategy for the application of interfluorophore TSET for construction of efficient organic triplet emitters. After demonstrating that thiophene-and selenophene-comprising hetroaromatic compounds covalently tethered with fluorescent dyes reveal intense long-lifetime PL if associated with PKs, [16][17][18] we assumed that similar or even more intense PL of these compounds might occur in solid matrices where access of quenching molecular oxygen and molecular movements of the luminophores would be limited. Polyvinyl alcohol (PVA) was selected as the solid matrix for these studies as this polymer is water soluble, transparent for near-UVand visible radiation, and can restrict diffucion molecular oxygen into the structure.…”
Section: Introductionmentioning
confidence: 99%
“…Oxazoline formation and subsequent oxidation provided ketone 3,4-NSN. A similar procedure was applied for selenadiazole including selenium incorporation, 28 oxazoline formation and oxidation to ketone 3,4-NSeN. To our surprise, during oxazoline formation to selenadiazole 9 a partial selenium-sulfurexchange has taken place, yielding 7 in moderate yield.…”
Section: Resultsmentioning
confidence: 95%
“…A slightly modified literature procedure was used. 28 3,4-Diaminobenzoic acid (1.22 g, 8.00 mmol, 1.00 eq) was dissolved in hydrochloric acid (26.7 mL, 0.3 M, 1.0 M in H2O) and heated to 80 °C (oil bath temperature). To the brownish solution was added a solution of SeO2 (1.78 g, 16.0 mmol, 2.00 eq), dissolved in water (12 mL), via Pasteur pipette within one minute.…”
Section: Benzo[c][125]selenadiazole-5-carboxylic Acid (8)mentioning
confidence: 99%
“…Although effective, this method is rather time-consuming because it includes three incubation steps of 1 h each and several washes [16]. Recently, fluorescence anisotropy (FA)-based assays using fluorophore-labeled inhibitors have been applied to investigate the binding of compounds directed at the active site of CK2a and other kinases [23][24][25][26][27][28]. This nonradioactive technique is highly suitable for high-throughput screening (HTS) and drug discovery [29,30].…”
Section: Introductionmentioning
confidence: 99%